The Effect of Education Level on the Performance of Health Workers at UPTD North Cimahi Health Center - Gema Putra Bangsa; Erliany Syaodih; Rian Andriani (Universitas Pendidikan Indonesia, 2023)
Employee education level is an important factor affecting work productivity. The level of education possessed by a person will affect the mindset, attitudes, and behaviors that are believed to increase productivity in order to achieve the set targets. This study aims to find out and analyze the influence of education level on the performance of health workers at the North Cimahi Health Center, UPTD Cimahi City. The research method used is a quantitative descriptive survey method. The population in this study was all UPTD Puskesmas employees in North Cimahi, with a total sample size of 25 people. Data collection techniques included observation, interviews, documentation, and questionnaires. The findings of this study indicate that the level of education has a positive influence on the education level and performance of health workers in North Cimahi, with a t-count value of 7.512, a t-table value of 2.07 indicating that t-count t-table, and a probability of 0.000 0.05.